Research and publication ethics: pillars of integrity in the scientific medical journal - Pradhan, Nabees Man Singh (Journal of Patan Academy of Health Sciences, 2023)
Research has been the foundation upon which human development has always been built. For sustainable growth, this foundation needs to be based on trustworthy knowledge, which cannot be achieved without following ethical standards at the highest possible level. Research has been conducted in various forms at different levels across all fraternities. There is no small or big research, there is only reliable or unreliable research. Research at different levels yields different levels of evidence which often builds up enough material to define a course of action, leading to the formation of guidelines or protocols.